2013
DOI: 10.1111/ijcp.12319
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term testosterone therapy in hypogonadal men ameliorates elements of the metabolic syndrome: an observational, long‐term registry study

Abstract: AimThe goal of this study was to determine if long-term testosterone (T) therapy in men with hypogonadism, henceforth referred to as testosterone deficiency (TD), ameliorates or improves metabolic syndrome (MetS) components.MethodsWe performed a cumulative registry study of 255 men, aged between 33 and 69 years (mean 58.02 ± 6.30) with subnormal plasma total T levels (mean: 9.93 ± 1.38; range: 5.89–12.13 nmol/l) as well as at least mild symptoms of TD assessed by the Aging Males' symptoms scale. All men receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
138
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(157 citation statements)
references
References 128 publications
15
138
0
2
Order By: Relevance
“…Androgen deficiency and low circulating T levels have been demonstrated to be independently associated with NAFLD/NASH (Kim et al, 2012;Völzke et al, 2010). Recently, several reports demonstrated that raising serum T concentrations to normal levels in hypogonadal patients by treatment with parenteral T, along with improving metabolic profile, significantly reduces the levels of liver transaminases (Haider et al, 2010;Traish et al, 2013), and circulating TNFa levels (Kalinchenko et al, 2010). In a randomized, double-blind, placebo-controlled study, Hoyos and colleagues showed that 18-week treatment with T significantly reduces liver fat content, as well as decreased arterial stiffness (Hoyos et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Androgen deficiency and low circulating T levels have been demonstrated to be independently associated with NAFLD/NASH (Kim et al, 2012;Völzke et al, 2010). Recently, several reports demonstrated that raising serum T concentrations to normal levels in hypogonadal patients by treatment with parenteral T, along with improving metabolic profile, significantly reduces the levels of liver transaminases (Haider et al, 2010;Traish et al, 2013), and circulating TNFa levels (Kalinchenko et al, 2010). In a randomized, double-blind, placebo-controlled study, Hoyos and colleagues showed that 18-week treatment with T significantly reduces liver fat content, as well as decreased arterial stiffness (Hoyos et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Homens portadores de Síndrome Metabólica (SM) são mais suscetíveis a desenvolverem DE 10,11,18,29,30 . Uma pessoa que possui mais de três aspectos metabólicos alterados citados a seguir pode ser diagnosticada como portadora de SM: obesidade central (circunferência da cintura superior a 88 cm na mulher e 102 cm no homem), hipertensão arterial sistêmica (pressão arterial sistólica > 130 e/ou pressão arterial diastólica > 85 mmHg), glicemia alterada (glicemia > 110 mg/dl) ou diagnóstico de diabetes, triglicerídeos > 150 mg/dl, HDL colesterol < 40 mg/dl em homens e < 50 mg/dl em mulheres [31][32][33] . Dados de 100 homens com SM apresentaram elevada prevalência de DE, quando comparados a homens que não possuíam a síndrome (26.7% vs 13%, p=0,03) 34 .…”
Section: Etiologia Endócrinaunclassified
“…19,20 Androgen deficiency promotes the production of fat cells, which contributes to obesity and the metabolic syndrome. 21 It also results in impaired glucose metabolism, higher levels of triglycerides and cholesterol, and lower levels of high-density lipoprotein (HDL) cholesterol, which are all features of the metabolic syndrome.…”
Section: The Link Beween the Metabolic Syndrome And Hypogonadismmentioning
confidence: 99%
“…This widespread effect was attributed to common mechanisms of action linking the pathophysiology of both conditions. 21 A small study analysed the effects of supervised diet and exercise with or without transdermal testosterone on components of the metabolic syndrome in hypogonadal men with this syndrome and newly diagnosed type 2 diabetes. After 52 weeks of treatment, 81% of men receiving testosterone no longer met the criteria of the metabolic syndrome versus 31% of those who did not receive testosterone.…”
mentioning
confidence: 99%